Macroalga-Derived Alginate Oligosaccharide Alters Intestinal Bacteria of Atlantic Salmon - Gupta, Shruti; Lokesh, Jep; Abdelhafiz, Yousri; Siriyappagouder, Prabhugouda; Pierre, Ronan; Sørensen, Mette; Fernandes, Jorge M. O.; Kiron, Viswanath (Frontiers in Microbiology, 2019)
Prebiotics are substrates intended to sculpt gut microbial communities as they are selectively utilized by the microorganisms to exert beneficial health effects on hosts. Macroalga-derived oligosaccharides are candidate prebiotics, and herein, we determined the effects of Laminaria sp.-derived alginate oligosaccharide (AlgOS) on the distal intestinal microbiota of Atlantic salmon (Salmo salar). Using a high-throughput 16S rRNA gene amplicon sequencing technique, we investigated the microbiota harboured in the intestinal content and mucus of the fish offered feeds supplemented with 0.5 and 2.5% AlgOS. We found that the prebiotic shifts the intestinal microbiota profile; alpha diversity was significantly reduced with 2.5% AlgOS while with 0.5% AlgOS the alteration occurred without impacting the bacterial diversity. Beta diversity analysis indicated the significant differences between control and prebiotic-fed groups. The low supplementation level of AlgOS facilitated the dominance of Proteobacteria (including P. phosphoreum, A. parvum, A. insolitus), and Spirochaetes (B. andersonii) in the content or mucus of the fish, and few of these bacteria (A. logei, A. parvum, B. andersonii, A. insolitus) have genes associated with butyrate production. The results indicate that the low inclusion of AlgOS can plausibly induce a prebiotic effect on the distal intestinal microbiota of Atlantic salmon. These findings can generate further interest in the potential of macroalgae-derived oligosaccharides for food and feed applications.